Análisis de demanda del sistema eléctrico en la empresa aromas del tungurahua, ubicada en Ambato, utilizando el software de simulación Neplan, para determinar el nivel de cargabilidad del sistema y realizar propuestas de mejora - Flores Quistial, Cristian Gustavo (2016)
The present work is intended to satisfy the need of the Aromas de Tungurahua enterprise, since, the state was not known, which was operating the factory, nor was available a study to plan an increase in demand, in such a virtue was made a study of the demand, to the electrical system. It was necessary to make a load census that allows us to quantify the installed potency, which was available on the installations and the total capacity of system with the help of NEPLAN software was performed power flow to determine the chargeability level its installations. To setting the system demand was necessary to use a load analyzer, since with the procured measurements for seven days were achieved to record the weekly load curve, voltage levels, potencies, power factor, streams and consumption. With the completion of this work was achieved to solve a need and implement the developed knowledge in areas such as industrial facilities, power quality, electrical circuits and SEP planning.